The complete mitochondrial genome data of Zhangixalus omeimontis (Anura: Rhacophoridae): genome characterization and phylogenetic considerationZenodo data - Qinggang Mei; Yi Qing; Yiming Deng; Dongmei Zhao; Lichun Jiang (Data in Brief)
Mitochondrial genomes in frogs are crucial in reconstructing phylogenetic relationships and clarifying molecular evolution in these animals. Therefore, we determined and analyzed the complete mitochondrial genome sequence of Zhangixalus omeimontis in this research. The total length of this sequence is 19,782 base pairs, containing a total of 37 genes, which include 22 tRNA genes, 13 protein-coding genes, and 2 rRNA genes, along with two D-loop regions. The mitochondrial genome exhibits a novel rearrangement pattern (tRNASer-ND6-tRNAGlu-Cytb-CR1-ND5-CR2-tRNAThr-tRNALeu-tRNAPro) of genes. The nucleotide base composition of the mitochondrial genome consists of 32.51 % adenine (A), 31.32 % thymine (T), 21.95 % cytosine (C), and 14.21 % guanine (G), exhibiting a bias towards AT content (63.83 %). The phylogenetic tree is constructed using the Bayesian inference (BI) and maximum likelihood (ML) methods. The findings indicated a close relationship between Z. omeimontis and Z. dugritei. The comprehensive mitochondrial genome of Z. omeimontis will be a valuable asset for forthcoming research endeavours focusing on the evolution, taxonomy, and genetic preservation of Zhangixalus.